REVERSE TRANSCRIPTASE POLYMERASE CHAIN REACTION (RT-PCR) BASED DETECTION OF PVSO AND PVSA STRAINS BY USING DEGENERATE PRIMERS - Kaushal, Nimisha; Gawande, S J; Kaundal, Priyanka; Garg, I D (Potato Journal, 2013)
Reverse transcriptase polymerase chain reaction (RT-PCR) procedure for the detection of both the strain groups PVSo and PVSA of PVS was developed and validated by testing isolates of both the strains as well as mericlones of potato variety Kufri Chipsona-3. Sensitivity and reliability of the technique was compared with that of ELISA and immuno electron microscopy (IEM). The technique was more sensitive and reliable than ELISA, but at par with IEM.